Computer modeling of the global warming effect (abstract) - Washington, W. M.; Dietterich, T. (Proceedings of the 1993 ACM/IEEE conference on Supercomputing, 1993)
Summary form only given, as follows. The state of knowledge of global warming will be presented and two aspects examined: observational evidence and a review of the state of computer modeling of climate change due to anthropogenic increases in greenhouse gases. Observational evidence, indeed, shows global warming, but it is difficult to prove that the changes are unequivocally due to the greenhouse-gas effect. Although observational measurements of global warming are subject to "correction," researchers are showing consistent patterns in their interpretation of the data. Since the 1960s, climate scientists have been making their computer models of the climate system more realistic. Models started as atmospheric models and, through the addition of oceans, surface hydrology, and sea-ice components, they then became climate-system models. Because of computer limitations and the limited understanding of the degree of interaction of the various components, present models require substantial simplification. Nevertheless, in their present state of development climate models can reproduce most of the observed large-scale features of the real system, such as wind, temperature, precipitation, ocean current, and sea-ice distribution. The use of supercomputers to advance the spatial resolution and realism of Earth-system models will also be discussed.